Treating Patients With Co-occurring Autism Spectrum Disorder and Substance Use Disorder: A Clinical Explorative Study. (April 2019) - Helverschou, Sissel Berge; Brunvold, Anette Ræder; Arnevik, Espen Ajo
Background: Substance use disorders (SUDs) have been assumed to be rare in individuals with autism spectrum disorder (ASD). Recent research suggests that the rates of SUD among individuals with ASD may be higher than assumed although reliable data on the prevalence of SUD in ASD are lacking. Typical interventions for SUD may be particularly unsuitable for people with ASD but research on intervention and therapy are limited. Methods: This study addresses ways of improving services for individuals with ASD and SUD by enhancing the competence of professionals in ordinary SUD outpatient clinics. Three therapists were given monthly ASD education and group supervision. The participants were ordinary referred patients who wanted to master their problems with alcohol or drugs. Four patients, all men diagnosed with ASD and intelligence quotient (IQ) ⩾ 70 completed the treatment. The participants were given cognitive behavioural therapy (CBT) modified for their ASD over a minimum of 10 sessions. The therapies lasted between 8 and 15 months. Standardised assessments were conducted pre- and post-treatment. Results: Post-treatment, 2 participants had ended their drug and alcohol abuse completely, 1 had reduced his abuse, and 1 still had a heavy abuse of alcohol. Physical well-being was the most prevalent reported positive aspect of drug or alcohol use, whereas the experience of being left out from social interaction was the most frequent negative aspects of intoxication. Conclusions: CBT may represent a promising treatment option for individuals with ASD and SUD. The results suggest that patients' symptoms can be reduced by providing monthly ASD education and group supervision to therapists in ordinary SUD outpatient clinics. This group of patients need more sessions than other client groups, the therapy has to be adapted to ASD, ie, direct, individualised, and more extensive. Moreover, the patients need psychoeducation on ASD generally, social training, and support to organise several aspects of their lives and some patients need more support than can be provided in an outpatient clinic.